Eksplorasi Data Hasil Survei Persepsi terhadap Rektor Dengan Metode Quota Sampling - Muhamad Fickri Ramadhan; . Erfiani; Farit Mochammad Afendi (Xplore: Journal of Statistics, 2018)
Rector functions as the executive leadership of Institut Pertanian Bogor, making strategic decisions and leading every element of IPB to achieveits short-term and long-term goals. Therefore, the Rector chosen by the election in 2017 has to synergize to human element of IPB to achieve the best organizational performance. This research by the means of survey is intended to gather information about the characteristics of an idealized Rector from the perspective of the academics, between the students, lecturers, and the administrative workers. Using quota sampling, descriptive statistics is used to describe the information about aspects such as character, leadership styles, and other factors that contribute to their preference. The information about the previous rector’s program is also gathered by this survey.